Stroke Outcomes With Vorapaxar Versus Placebo in Patients With Acute Coronary Syndromes: Insights From the TRACER Trial - Leo Ungar; Robert M. Clare; Fatima Rodriguez; Bradley J. Kolls; Paul W. Armstrong; Philip Aylward; Claes Held; David J. Moliterno; John Strony; Frans Van de Werf; Lars Wallentin; Harvey D. White; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Vorapaxar, a protease‐activated receptor‐1 antagonist, is approved for secondary prevention of cardiovascular events but is associated with increased intracranial hemorrhage. Methods and Results TRACER (Thrombin Receptor Antagonist for Clinical Event Reduction in Acute Coronary Syndrome) was a trial of vorapaxar versus placebo among patients with acute coronary syndrome. Strokes were adjudicated by a central events committee. Of 12 944 patients, 199 (1.5%) had ≥1 stroke during the study period (median follow‐up, 477 days). Four patients had a single stroke of unknown type; 195 patients had ≥1 stroke classified as hemorrhagic or nonhemorrhagic (165 nonhemorrhagic, 28 hemorrhagic, and 2 both). Strokes occurred in 96 of 6473 patients (1.5%) assigned vorapaxar and 103 of 6471 patients (1.6%) assigned placebo. Kaplan‐Meier incidence of stroke for vorapaxar versus placebo was higher for hemorrhagic stroke (0.45% versus 0.14% [hazard ratio, 2.74; 95% confidence interval, 1.22–6.15]), lower but not significantly different for nonhemorrhagic stroke (1.53% versus 1.98% at 2 years [hazard ratio, 0.79; 95% confidence interval, 0.58–1.07]), and similar for stroke overall (1.93% versus 2.13% at 2 years [hazard ratio, 0.94; 95% confidence interval, 0.71–1.24]). Conclusions Stroke occurred in <2% of patients. Vorapaxar‐assigned patients had increased hemorrhagic stroke but a nonsignificant trend toward lower nonhemorrhagic stroke. Overall stroke frequency was similar with vorapaxar versus placebo.